Zosteriform idiopathic atrophoderma of Pasini and Pierini - Tasleem Arif (Wolters Kluwer Medknow Publications, 2019)
Idiopathic atrophoderma of Pasini and Pierini (IAPP) is a rare disease of unknown etiology characterized by well-defined atrophic plaques with a "cliff-drop" border that show no signs of inflammation, sclerosis, and induration. The trunk is most commonly affected site. It usually affects the body in a bilaterally symmetrical distribution, although asymmetric involvement has also been reported. Very few cases occurring in a zosteriform distribution have been reported. In this article, the author reports a rare case of IAPP in an 18-year-old male where the lesions are distributed in a zosteriform distribution on the trunk.